2021
DOI: 10.1002/cbic.202100232
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Chirality in Phospholipid Membranes

Abstract: Nucleotides, amino acids, sugars, and lipids are almost ubiquitously homochiral within individual cells on Earth. While oligonucleotides and proteins exist as one natural chirality throughout the tree of life, two stereoisomers of phospholipids have separately emerged in archaea and bacteria, an evolutionary divergence known as "the lipid divide". Within this review, we focus on the emergence of phospholipid homochirality and compare the stability of synthetic homochiral and heterochiral membranes in vitro. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Chiral lipid membranes can discriminate between amino acid enantiomers. A natural cellular membrane interacts more favorably with the L-enantiomer than the D amino acid [ 31 ]. Using a computer simulation, Chen et al have shown that L-peptides are absorbed easily by natural POPC membranes, but the D-peptides have to overcome an extra free-energy barrier [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral lipid membranes can discriminate between amino acid enantiomers. A natural cellular membrane interacts more favorably with the L-enantiomer than the D amino acid [ 31 ]. Using a computer simulation, Chen et al have shown that L-peptides are absorbed easily by natural POPC membranes, but the D-peptides have to overcome an extra free-energy barrier [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that membrane lipids and amino acids are almost ubiquitously homochiral within individual cells on Earth. A number of studies try to elucidate the determinants of stereospecific interactions between lipids, amino acids, and chiral drug molecules (see for example review [ 31 ]). Taking into account the results of previous studies of photoinduced electron transfer in diastereomers ketoprofen-tryptophan, in the present study we also use S-ketoprofen as an electron acceptor in photoinduced interaction with enantiomers of tryptophan, and CIDNP technique (chemically induced dynamic nuclear polarization) and molecular dynamics (MD) to study the peculiarities of their interaction in lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…autophagy, apoptosis, cell growth, proliferation, and functions [145]. As a key component of cellular metabolism, mTOR integrates environmental stressors demand), cell physiology, and organism behavior.…”
Section: Universal Biological Of Agingmentioning
confidence: 99%
“…chirally matched combinations would have conducted to potent living systems whilst the chirally mismatched combinations would have declined. Such theory has notably been proposed recently to explain the splitting of lipids into opposite configurations in archaea and bacteria (known as the 'lipide divide') 521 and their persistence. 522 However, these theories do not address the fundamental question of the initial chiral bias and its enhancement.…”
Section: 520mentioning
confidence: 99%